Role of Innate lymphoid Cells in Obesity and Insulin Resistance - Chen, Hong; Sun, Lijun; Feng, Lu; Yin, Yue; Zhang, Weizhen (Frontiers in Endocrinology, 2022)
Obesity, a growing chronic metabolic disease, greatly increases the risk of metabolic syndrome which includes type 2 diabetes, fatty liver and cardiovascular diseases. Obesity-associated metabolic diseases significantly contribute to mortality and reduce life expectancy. Recently, innate lymphoid cells (ILCs) have emerged as crucial regulators of metabolic homeostasis and tissue inflammation. This review focuses on the roles of ILCs in different metabolic tissues, including adipose tissue, liver, pancreas, and intestine. We briefly outline the relationship between obesity, inflammation, and insulin resistance. We then discuss how ILCs in distinct metabolic organs may function to maintain metabolic homeostasis and contribute to obesity and its associated metabolic diseases. The potential of ILCs as the therapeutic target for obesity and insulin resistance is also addressed.